Democracy and Identity: Liberal Virtue and the Hybrid Individual - Kook, Rebecca (Hagar: Studies in Society and Culture, 2002)
Democratic politics, at the dawn of the 21st century, is faced with new and seemingly insurmountable problems. The declining significance of national sovereignty, the growing pervasiveness of human, political and social rights abuses and the increasing appeal of exclusionary identities are posited against the rise of transnational political actors and trends, the globalization of economies and the expansion of global networks of information and media. These developments have seriously challenged existing conceptions of individual and collective identity and the ways in which they interact.